Highly charged ions in Penning traps: a new tool for resolving low-lying isomeric states - Gallant, Aaron; Simon, Vanessa Véronique; Simon, Martin C. (Physical review. C, Nuclear physics, 2012)
The use of highly charged ions increases the precision and resolving power, in particular for short-lived species produced at on-line radio-isotope beam facilities, achievable with Penning trap mass spectrometers. This increase in resolving power provides a new and unique access to resolving low-lying long-lived (T1/2>50 ms) nuclear isomers. Recently, the 111.19(22) keV (determined from γ-ray spectroscopy) isomeric state in 78Rb was resolved from the ground state, in a charge state of q=8+ with the TRIUMF Ion Trap for Atomic and Nuclear science at the TRIUMF's Isotope Separator and Accelerator facility. The excitation energy of the isomer was measured to be 108.7(6.4) keV above the ground state. The extracted masses for both the ground and isomeric states, and their difference, agree with the ame2003 and Nuclear Data Sheet values. This proof of principle measurement demonstrates the feasibility of using Penning trap mass spectrometers coupled to charge breeders to study nuclear isomers and opens a new route for isomer searches.